The Authority of Habitus in Contemporary Relational Art (Al-Academy, 2026)
This research is concerned with studying (the authority of habitus and its effects on contemporary relational art). It consists of four chapters. The first chapter is devoted to explaining the research problem, its importance and need, the goal, and the temporal and spatial limits, in addition to defining the terms of the research title. The research problem sheds light on the importance of habitus as it is not just a set of individual behaviors, Rather, it reflects the larger social structures and power relations among humans, and plays a crucial role in replicating social differences and maintaining their structure. As is known, the interactive or participatory audience is made up of groups that influence each other, as a result of the collective social influence, which is based on the idea of relational art, Although people are influenced by the majority of the group to engage in certain behaviors, which may be atypical for them, they are influenced by being part of a group. The research problem leads to the question: (Does the authority of habitus fulfill the condition of social participation for the recipients within the structure of the relational artwork?), and (Chapter Two) of this research included the theoretical framework, Two chapters: The first chapter, entitled (The concept of hypotheses and its impact on the idea of interrelationship), and the second chapter, which was complementary, was entitled (Relational art - the theory of contemporary relational aesthetics), As for (Chapter Three), it was devoted to the research procedures that included the research community, and the researcher selected her research sample from the entire community as a whole, with (three samples) intentionally, which were analyzed and compared based on what she arrived at from a set of indicators of the theoretical framework, While (Chapter Four) was devoted to the results and conclusions produced by the research, the most important of which were:1- Relational art requires the artist not to be present, or to somehow be able to step back enough to become equal with the participants.2- There are different degrees of relational engagement, ranging from intellectual manipulation to symbolic consultation.3- Relational artwork is, in fact, the audience's interactions with the situation